Sensory Acceptability of Sweet Potato (Ipomoea batatas) and Carrot (Daucus carota) Fries Enriched with Moringa oleifera - Magtubo, Jovan; Semillano, Cindy; Macario, Trisha Mae; Reyes, Paloma Marie Therese; Torres, Dorelyn; Owa, Michelle Rose; Millondaga, Reynold (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the acceptability of sweet potato (Ipomoea batatas) and carrot (Daucus carota) fries enriched with Moringa oleifera as a functional snack alternative. Anchored on the theory of sensory evaluation, the study employed a quasi-experimental research design involving three formulations evaluated using a researcher-made questionnaire with a 9-point hedonic scale. The respondents consisted of sixty-five third-year Bachelor of Science in Hospitality Management students selected through purposive sampling. Data were analyzed using mean, standard deviation, and Analysis of Variance (ANOVA) to assess differences in appearance, aroma, taste, texture, and general acceptability. The results showed that all formulations were generally well accepted, with Formulation 2 consistently obtaining the highest ratings across all sensory attributes. No significant differences were found in appearance, taste, texture, and general acceptability, while a significant difference was observed only in aroma. These findings indicate that the incorporation of Moringa oleifera did not compromise sensory quality and that Formulation 2 achieved the most balanced sensory profile. The study concludes that moringa-enriched sweet potato and carrot fries are acceptable and suitable for product development and potential commercialization. This study aligns with Sustainable Development Goal 3 (Good Health and Well-Being) and Sustainable Development Goal 12 (Responsible Consumption and Production) by promoting healthier snack alternatives and encouraging the use of locally available ingredients. It contributes to sustainability by supporting improved dietary practices and enhancing the utilization of local agricultural resources for food innovation.